The Post-Human Society. Elemental Contours of the Aesthetic Economy of the United States - Kanth, Rajani (De Gruyter, 2015)
The Post-Human Society is a rich, unique, path-breaking, belletristic and literary 'crie de coeur' work - a lyrical expose of all the internal infelicities (social, political, aesthetic) of the United States of America. In its vivid contrasting of the mores of competition, avarice, and greed to communitarian, co-respecting and co-operative values, it abounds with colorful, vibrant, breathtaking images and tropes. Utilizing a novel, First Person Narrative, the author Rajani Kanth offers a poignant critique of the rabid, runaway materialism that has been the bane of all modernist, European societies, to date. It is evocative in its approach to the fading genre of the iconic anthropology/sociology classics of the yesteryear.Ultimately, it is a critique of the ruling ethos of our times: Eurocentrism - i.e., selfish and acquisitive materialism, of which the contemporary USA is the trend-setter and the unchallenged gold standard. DR. RAJANI KANTH has an MA in Social Anthropology from the Delhi School of Economics, India, and a PhD in Economics from the New School for Social Research, New York, USA. After serving as Economic Advisor to the UN in New York, he taught as University Professor, and is currently based at Harvard University.